(untitled) (Fiep Bulletin - online, 2013)
The average Soccer can never be confused with the Swiss Soccer or the Society Soccer, regarding the register such before. Its origin occurred between late 1965, when the gentlemen Hamilton and Di Stéfano Paschoal Milton Paschoal Lentini, citizens of Lucélia lovers of football and sport, decided to edit the document in its entirety with the rules of the game of average football, being recorded in the Registry Cort of Deeds and Documents of the District of Lucélia under no. 185 of the book "E" and published in the Official Gazette of the State of São Paulo, in not published notebook on page 2 of the day March 18, 1978, which provides for the 18 game rules, field size, ball, and other details that differ the style of average football of other modalities.In a short time the average soccer gained wide dissemination of the Regional Newspapers and Magazine "O Divulgador" and Radio Bandeirantes of São Paulo, released across the country through the voice of renowned broadcaster Fiori Gigliotti, that Wednesday was a review of all-round Saturday and Sunday League who performed in the city of Lucélia, forcing the farthest cities from Brazil were answered in their requests for Rules Average Football. From 1967 it was a fever throughout the region and even in other states began to search for the average soccer practice, interested in the official rules, which through comments, were spread across the region becoming pervasive, thus becoming, rules officers who dominated most of the country.Due to evolution of customs, consumer goods and more advanced technologies, the rules had to be suit to the circumstances and have undergone some changes, with the goal of providing the modality, a more panoramic vision and more dynamic level such as the current Football Field without losing the charm, elegance and unique style of game.After committed changes, the rules again were recorded in the Registry as set out in Book B - 133, registered under no. 6548, on 18 May 2010.Today recognized worldwide average football is a sport practiced by all, with easy access, few financial costs; many places do not even know its real ideology. Like all other sports, does not discriminate between social class and any pre-concept to humans, such as formalizing a competitive or recreational.